Comparative genomics and phylogenomics of Mycobacterium tuberculosis with a special emphasis on Mycobacterium africanum - (:unkn) unknown (My University, 2023)
Over the decades humans have been affected by tuberculosis (TB) for millennia. For centuries, TB remains a global health crisis and the leading cause of mortality due to a single infectious agent. Human TB is primarily caused by Nine human adapted phylogenetic lineages of Mycobacterium tuberculosis complex (MTBC). Importantly, variation in MTBC lineages is known to impact TB infection and is clinically driven by ecological distribution, and partly reflecting human demographic histories. Mycobacterium africanum (Maf) is mainly restricted to West and part of Central Africa for reasons that are not well deciphered but one possibility might be that MAF is adapted to the distinct human population (s) in West Africa. Previous studies have described distinct phenotypic characteristics such as the association of Maf L5 with ethnicity whereas Maf L6 has been associated with HIV infection and slower progression to active disease. Studies have been made to further explore these observations with comparative genomics and molecular epidemiology with limited phenotypic studies. Some studies involving Maf L6 showed characteristics such as slow growth, preference for pyruvate as a carbon source in a liquid medium, and, dysgonic growth nature in a solid medium. The observed diversity in the phenotypic and genotypic profiles of MTBC could influence the outcome of TB disease. The relevance of genomics became the order to explore the composition and diversity of Maf and to differentiate between Lineage 5 and Lineage 6, as these lineages differ in associated patient variables. Comparative genomics of Mycobacterium africanum connotes the study of the genomic structure, gene content, and phylogenetic relationships of this subspecies of Mycobacterium tuberculosis complex bacteria. It is a major cause of tuberculosis in West Africa and is classified into two lineages known as M. africanum Lineage 5 and lineage 6. Several studies have identified several genomic regions unique t
Keywords: African Research